Pengembangan Sistem Informasi Dokumentasi Kegiatan Dinas Pemberdayaan Masyarakat dan Desa Kota Gunungsitoli - Laoli, Hendra Sahputra; Lase, Devi Chrisman; Telaumbanua, Aldin Noferman; Zebua, Supriyadi (Jurnal Sains dan Teknologi (JSIT), 2025)
The main problem in managing activity documentation at the Community and Village Empowerment Office (PMD) of Gunungsitoli City is the unavailability of a comprehensive and integrated digital system capable of recording, storing, and presenting activity data in a systematic, structured, and easily accessible manner. This limitation causes the data retrieval process to be time-consuming, increases the risk of information loss, and reduces efficiency in supporting both administrative tasks and decision-making processes. Without a proper digital platform, the management of documents and activity records relies heavily on manual processes, which often lead to duplication of work and difficulties in tracking historical data. This study aims to design and develop a web-based activity documentation information system that can support, streamline, and improve the effectiveness and efficiency of data management. The system is intended to ensure data security, accessibility, and accuracy while meeting the operational needs of the institution. The research method applied is Research and Development (R&D) using a waterfall approach, which includes requirements analysis, system design, implementation, and testing phases. The system was developed with the CodeIgniter 3 framework, MySQL database, and Bootstrap Unicat interface template, running on the XAMPP platform. The results indicate that the developed system effectively facilitates documentation management, supports multi-level user authentication, enables fast and accurate data retrieval, and improves data accessibility for internal offices and relevant stakeholders. It also enhances information security through layered authentication and provides a responsive, user-friendly interface. The study concludes that this web-based documentation information system is an effective, efficient, and reliable digital solution for the PMD Office of Gunungsitoli City, with future development possibilities including integration with other systems and advanced data analytics features.